HIGH SKILLS/GIFTEDNESS: AN INTEGRATIVE REVIEW - da Silva Lopes, Erivelton; Helga de Souza Rodrigues da Silva, Kezya; Mescouto Miranda, Aquila; Luzia Caldas de Brito, Wanda; Kalinka Brito do Carmo, Ingrid; Coelho Martins, Suelene; Maria Sousa de Queiroz, Joseane; de Almeida Cavalcante Assis, Camila; Sintia Redig de Oliveira, Germana; da Costa Lopes, Eliane (Revista Gênero e Interdisciplinaridade, 2025)
In Brazil, since 2008, students with high abilities/giftedness have been included in the Special Education modality, but despite the legal guarantees achieved, it is observed that the school community does not notice many students, therefore their needs are not met. The methodology consisted of a bibliographic survey of national articles published and indexed in the following databases: CAPES Journal Portal, Science Direct/Elsevier and SciELO (Scientific Electronic Library Online), adopting the following descriptors: high abilities/giftedness, talent, identification, recognition, screening, characteristics and teacher training, totaling 23 articles for analysis. Given this, it is concluded that teacher training appears as the most important topic in this analysis, because as inclusion policies lead to significant changes in education in order to clarify, adequately equip the teaching staff and improve service to students with high abilities/giftedness, as learning experiences aimed at their full development will be very rich.